An environmental court in action : function, doctrine and process - Preston, Brian; Fisher, Elizabeth C (London [England] : Hart Publishing, 2022)
"This book provides a critical assessment of the New South Wales Land and Environmental Court (NSWLEC). Effective adjudication has become a key consideration for environmental lawyers. One of the most important questions is whether environmental law frameworks need their own courts, with the conclusion being: yes they do. Here, a pioneer of such a court, the NSWLEC is forensically examined to see what it might teach other such courts. Showing a court 'in action' it suggests models that practitioners and policy makers might follow. It also speaks to the environmental law scholars, setting out a conceptual framework for studying such courts as legal institutions. This multi-faceted collection is invaluable to scholars and practitioners alike."--
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: New South Wales. -- Land and Environment Court; Environmental law -- Australia -- New South Wales; Courts of special jurisdiction -- Australia -- New South Wales; Electronic books